Directory of Open Access Journals outils webmaster Spatial Analysis of Vegetable Crops in Maysan Province - ذاكر توفيق, أ. د شهلة (lark, 2020)
:AbstractThis study is based on knowledge of spatial analysis of vegetable crops cultivation in Maysan governorate between the district and other districts. Vegetable crops were represented on the basis of unit area, production and yield was used logarithmic conversion technology in the use of the unit area and production and technology of equal lengths in Representation of productivity has been represented on maps.
Keywords: Key words: ( Vegetable, area, production ,Family, map).